Setanaxib (GKT137831) Ameliorates Doxorubicin-Induced Cardiotoxicity by Inhibiting the NOX1/NOX4/Reactive Oxygen Species/MAPK Pathway - Zheng, Hui; Xu, Nannan; Zhang, Zihao; Wang, Fen; Xiao, Jie; Ji, Xiaoping (Frontiers in Pharmacology, 2022)
Background: Doxorubicin (DOX)-induced cardiotoxicity is a highly concerning issue, and the mechanism by which DOX induces cardiotoxicity is likely to be multifactorial. NADPH oxidase (NOX) is associated with DOX-induced cardiotoxicity. Setanaxib (GKT137831), a preferential direct inhibitor of NOX1 and NOX4, can delay or prevent the progression of many cardiovascular disorders by inhibiting reactive oxygen species (ROS) generation. In this study, we investigated the role of GKT137831 in ameliorating DOX-induced cardiotoxicity and the potential mechanisms of its action. Methods and Results: The mice model of cardiotoxicity induced by DOX was established, and GKT137831 treatment was performed at the same time. Neonatal rat cardiomyocytes (NRCMs) were treated with DOX or GKT137831 for in vitro experiments. We found that DOX administration impaired cardiac function in vivo, reflected by decreased left ventricular ejection fraction (LVEF) and fractional shortening (FS%). DOX also impaired the viability of NRCMs in vitro. In addition, DOX increased the levels of NOX1 and NOX4 expression and ROS production and the cardiomyocyte apoptosis rate, both in vivo and in vitro. GKT137831 improved cardiac function, as indicated by the increased LVEF and FS%. In vitro, GKT137831 improved NRCM viability. It also decreased ROS production and the cardiomyocyte apoptosis rate. Apoptotic indices, such as cleaved PARP (c-PARP), cleaved caspase 3 (CC3) and BAX expression levels, were decreased, and the antiapoptotic index of Bcl-2 expression was increased. DOX markedly activated phosphorylated JNK, ERK and p38 proteins in NRCMs. Specific inhibitors of JNK (SP600125), ERK (PD98059) or p38 (SB203580) inhibited DOX-induced apoptosis of NRCMs. GKT137831 pretreatment inhibited excessive DOX-induced MAPK pathway activation. Conclusion: This study revealed that GKT137831 can alleviate DOX-induced cardiomyocyte apoptosis by inhibiting NOX1/4-driven ROS production. The upregulation of MAPK pathway induced by NOX1/4-derived ROS production may be the potential mechanism of GKT137831 action. GKT137831 may be a potential drug candidate to ameliorate DOX-induced cardiotoxicity.